2016
DOI: 10.1161/circresaha.115.307738
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10-Dependent Signaling Through Notch1 and Notch4 Controls Development of Organ-Specific Vascular Beds

Abstract: Rationale Endothelial Notch signaling is critical for early vascular development and survival. Yet, previously described mice lacking endothelial ADAM10 (a disintegrin and metalloproteinase 10), a key regulator of Notch signaling, survived into adulthood with organ-specific vascular defects. These findings raised questions about whether these vascular defects were related to Notch signaling or other functions of ADAM10. Objective Determine whether compensatory or redundant functions of ADAM17 in Notch signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 55 publications
1
56
0
Order By: Relevance
“…Genome-wide loss-of-function screens in HAP1 haploid or myeloid cells identified ADAM10 as a necessary factor in Hla-mediated cell death, and overexpression of ADAM10 lead to increased Hla binding and toxicity [114116]. Because ADAM10 is necessary for embryonic development and maintenance of the epithelium, in vivo studies are limited to the use of conditional or inducible ADAM10 knockout lines [117, 118]. Nevertheless, these studies have provided valuable insights which are discussed in detail below.…”
Section: Cell Surface Receptors For S Aureus Pftsmentioning
confidence: 99%
“…Genome-wide loss-of-function screens in HAP1 haploid or myeloid cells identified ADAM10 as a necessary factor in Hla-mediated cell death, and overexpression of ADAM10 lead to increased Hla binding and toxicity [114116]. Because ADAM10 is necessary for embryonic development and maintenance of the epithelium, in vivo studies are limited to the use of conditional or inducible ADAM10 knockout lines [117, 118]. Nevertheless, these studies have provided valuable insights which are discussed in detail below.…”
Section: Cell Surface Receptors For S Aureus Pftsmentioning
confidence: 99%
“…The biological link between TSPAN15 and VTE is still obscure. Of note, TSPAN15 has been shown to partner with ADAM10 to modulate the N‐cadherin adhesion molecule and to control vascular development (Alabi et al , ) as well as to act as a negative regulator of the Notch signalling pathway (Matthews et al , ), a key pathway controling angiogenesis (Benedito & Hellström, ). In addition, TSPAN15 contributes to the cleavage of platelets amyloid precursor protein (Matthews et al , ) whose regulation is proposed as a new player in the pathophysiology of VTE (Canobbio et al , ).…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%
“…Notch1 homozygous knockout mice are also embryonic lethal prior to E11 (Conlon et al, 1995;Swiatek et al, 1994), and this is recapitulated in processing-deficient Notch1 embryos (Huppert et al, 2000) and in Rbpj −/− embryos (Oka et al, 1995), indicating that canonical Notch1 signaling is required for vascular development and embryonic survival. However, endothelial deletion of Notch1 using a Tie2-Cre specifically expressed in endothelial cells is far less severe and 50% of these mice survive for at least 8 weeks, albeit with vascular anomalies (Alabi et al, 2016). This is in stark contrast to an earlier study in which the use of another Tie2-Cre strain (Limbourg et al, 2005) suggested that loss of endothelial Notch1 was the sole cause of embryonic death seen in null mice; however, it was subsequently noted that the Tie2 promoter used in this strain is also active in the female germ line (de Lange et al, 2008).…”
Section: Introductionmentioning
confidence: 99%